Strategically Prioritizing Type-Specific Innovations at the Stages of the Supply Chain Resilience Cycle: A Contingency Framework - Li, Bo (Journal of Strategic Innovation and Sustainability, 2024)
Faced with various disruptions and crises, supply chain decision-makers are eager to enhance their supply chain resilience (SCRES), and they have realized that innovation could be a powerful tool for enhancing SCRES. This paper investigates the relationship between innovation and SCRES by analyzing the types of innovation at the SCRES stages. We contend that innovation positively impacts SCRES if investment in type-specific innovation is strategically planned and prioritized. The proposed research framework demonstrates this relationship and guides how to prioritize type-specific innovation at each stage of the SCRES cycle. This research builds a foundation for future research on the interrelationship between innovation and SCRES. It offers supply chain practitioners a roadmap for investing in type-specific innovation at each stage of the SCRES cycle.